The prevalence of the hepatitis C virus among the conditionally healthy population of the Russian Federation - N. Soboleva V.; A. Karlsen A.; T. Kozhanova V.; V. Kichatova S.; V. Klushkina V.; O. Isaeva V.; M. Ignatieva E.; V. Romanenko V.; N. Oorzhak D.; E. Malinnikova Yu.; K. Kuregyan K.; M. Mikhailov I.; et al. (Journal Infectology, 2017)
Aim. To determine the prevalence of hepatitis C virus (HCV) in different age groups of the conditionally healthy population of Russia.Materials and methods. Total 4764 serum samples from a conditionally healthy population of five regions of Russia (Moscow, Rostov, Sverdlovsk regions, Tyva Republic, and Sakha Republic (Yakutia) were tested. The study included persons of 10 age groups: < 1 year, 1–4 years, 5–9 years, 10–14 years, 15–19 years, 20–29 years, 30–39 years, 40–49 years, 50–59 years old, ≥ 60 years. Anti-HCV was determined in ELISA with commercial test systems. Anti-HCV positive samples were tested for HCV RNA by RT-PCR. The genotype of HCV was determined based on the analysis of the nucleotide sequences of the core and NS5B regions of the viral genome.Results. The overall prevalence of anti-HCV in 5 regions of Russia was 2,6% (126/4764), and the proportion of people with HCV RNA was 1,1% (50/4764). The highest anti-HCV positivity rate was observed in Tyva and Yakutia (3,3% in both regions), in other regions its prevalence varied from 1,7% (Moscow region) to 3,0% (Sverdlovsk region). The highest frequency of HCV RNA detection was observerd in Tyva Republic and Rostov region (1.3% in both regions). No positive for HCV RNA cases was detected among persons aged 0–19 years in any region, except for Tyva Republic (1,0% (1/98) in age group 15–19 years). Peak positivity rates of HCV RNA were detected in the age groups 20–29 years and 30–39 years in the Rostov Region (3,9% and 3,0%, respectively); in Yakutia – in the group of 30–39 years (3,7%), in Tyva – in the group of 40–49 years (3,6%), in the Moscow region – in the groups of 20–29 and 30–39 years (2,9% and 2,5%, respectively).Conclusion. The results obtained indicate a high degree of HCV infection in virtually all age groups in the interval from 20 years to ≥60 years. Specific age cohorts that might benefit from inclusion in regional HCV screening programs were identified in each region. Цель. Определить долю инфицированных вирусом гепатита С (ВГС) лиц в различных возрастных группах условно здорового населения России.Материалы и методы. Исследованы 4764 образца сы- воротки крови от условно здорового населения пяти регионов РФ: Свердловской, Ростовской, Московской областей, Республики Тыва и Республики Саха (Якутия). В исследование были включены лица 10 возрастных групп: меньше 1 года, 1–4 года, 5–9 лет, 10–14 лет, 15–19 лет, 20–29 лет, 30–39 лет, 40–49 лет, 50–59 лет, старше 60 лет. Анти-ВГС определяли в ИФА с коммерческими тест-системами. В положительных по анти-ВГС образцах определяли РНК ВГС методом ОТ-ПЦР. Генотип ВГС определяли на основании анализа нуклеотидных последовательностей участков core и NS5B вирусного генома.Результаты. Общая распространенность анти-ВГС в 5 регионах РФ составила 2,6% (126/4764), доля лиц с РНК ВГС – 1,1% (50/4764). Наибольшая распространенность анти-ВГС выявлена в Республиках Тыва и Якутия (3,3%), в остальных регионах данный показатель варьировал от 1,7% (Московская область) до 3,0% (Свердловская область). Наибольшая частота выявления РНК ВГС отмечена в Республике Тыва и Ростовской области (1,3% в обоих регионах). Среди лиц в возрасте от 0 до 19 лет РНК ВГС не была выявлена ни в одном регионе, за исключением Республики Тыва (1% (1/98) в группе 15–19 лет). Пиковые показатели выявления РНК ВГС были вы- явлены в возрастных группах 20–29 лет и 30–39 лет в Ростовской области (3,9% и 3,0% соответственно); в Якутии – в группе 30–39 лет (3,7%), в Тыве – в группе 40–49 лет (3,6%), в Московской области – в группах 20–29 лет и 30–39 лет (2,9% и 2,5% соответственно).Заключение. Полученные результаты свидетельствуют о высокой степени пораженности ВГС практически всех возрастных групп в интервале от 20 лет до ≥ 60 лет. В каждом из обследованных регионов выявлены возрастные когорты, для которых целесообразно включение в региональные скрининговые программы.